2008
DOI: 10.1146/annurev.publhealth.29.020907.090954
|View full text |Cite
|
Sign up to set email alerts
|

Why Is the Developed World Obese?

Abstract: Obesity has risen dramatically in the past few decades. However, the relative contribution of energy intake and energy expenditure to rising obesity is not known. Moreover, the extent to which social and economic factors tip the energy balance is not well understood. This exploratory study estimates the relative contribution of increased caloric intake and reduced physical activity to obesity in developed countries using two methods of energy accounting. Results show that rising obesity is primarily the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
292
1
13

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(314 citation statements)
references
References 57 publications
8
292
1
13
Order By: Relevance
“…Results are also consistent with Bleich and colleagues, who have modelled the fraction of obesity due to energy in and energy out for a number of developed countries (10) . They concluded that physical activity in Canada did not change appreciably from 1990 to 2001, and 100 % of the attributable fraction of obesity was due to energy in rather than energy out.…”
Section: Discussionsupporting
confidence: 90%
“…Results are also consistent with Bleich and colleagues, who have modelled the fraction of obesity due to energy in and energy out for a number of developed countries (10) . They concluded that physical activity in Canada did not change appreciably from 1990 to 2001, and 100 % of the attributable fraction of obesity was due to energy in rather than energy out.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, this influence can be clearly seen as children are more likely to pick up items that are in "Mac Donald's" packaging (Robinson et al, 2007). More generally, Cutler et al (2003) and Bleich et al (2008) argue that the increased calorie intake (i.e., eating habits) plays a major role in explaining current obesity rates. Importantly, weight gain prior to adulthood set the stage for weight gain in adulthood.…”
Section: Previous Literaturementioning
confidence: 99%
“…Similar trends have been detected in Europe (4,5) . Since energy expenditure decreased only slightly over the same period (2) , the obesity problem is best described as an issue of systematic caloric overconsumption (6) , with snacking as an increasingly important contributor.Literature on the relationship between weight status and snacking behaviour is inconclusive (7) . This can partly be explained by the fact that weight status is not only influenced by snacking but also by factors such as meal consumption and physical activity.…”
mentioning
confidence: 99%
“…The origin of overweight and obesity lies primarily in an imbalance between the intake and the expenditure of energy (2) . During the last decades there has been an increase in daily eating occasions (3) and therewith daily energy intake has also increased.…”
mentioning
confidence: 99%